The Influence of the Application of the Science Technology Society Approach on Students' Science Process Skills in Science Learning - Asrial Asrial; Syahrial Syahrial; Husni Sabil; Ahmad Mansur Nawahdani; Miftahul Zannah Azzahra; Rezwanul Alam (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to analyze the influence of the Science Technology Society (STS) approach on improving students’ science process skills in science learning. The focus is to evaluate the impact of STS in improving skills such as observation, classification, interpretation, and communication of scientific findings. Methodology: This study used a quasi-experimental design with a pretest-posttest control group design. This study involved quantitative data analysis using t-test and N-Gain Score. Participants were students from selected junior high schools. The tools used included pretest and posttest instruments, along with an observation checklist. Main Findings: The study found a significant increase in science process skills in the experimental group using the STS approach. The experimental group had a higher mean posttest score (18.00) compared to the control group (17.00). The N-Gain score for the experimental group (0.53) was also significantly higher than the control group (0.25). Novelty/Originality of this study: This study introduces the systematic application of the STS approach to improve students’ science process skills. It offers new insights into how STS integration can create more engaging, relevant, and effective learning experiences. It contributes to the ongoing development of innovative context-based science education strategies.